Determining Criminal Actions in Corruption: The characteristics of Freies Ermessen Principles - Dijan Widijowati (Postgraduate of Jayabaya University, 2016)
The government is required to solve the dynamics of the problem quickly and precisely by deciding a policy even though it has no legal framework (freies ermessen). The implementation of freies ermessen in practice is often used as the basis of alleged corruption by Corruption Eradication Commission (CEC/KPK). The method used in the assessment is the normative juridical approach with literature approach. The implementation of freies ermessen has the risk of success and failure that could harm the state, but Corruption Eradication Commission should be able to consider the failure of the policy is part of the business in freies ermessen. Keywords: Corruption Eradication Commission , criminal act, freies ermessen.